Geoepidemiology of systemic vasculitis: comparison of the incidence in two regions of Europe. Issue 2 (1st February 2001) - Watts, R A; Gonzalez-Gay, M A; Lane, S E; Garcia-Porrua, C; Bentham, G; Scott, D G I
Abstract : OBJECTIVE: The aetiopathogenesis of the primary systemic vasculitides (PSV) is unknown but includes both environmental and genetic factors. The development of classification criteria/definitions for PSV allows comparison of the epidemiology between different regions. METHODS: The same methods and the American College of Rheumatology (1990) criteria or Chapel Hill definitions were used to compare the epidemiology of Wegener's granulomatosis, Churg-Strauss syndrome, microscopic polyangiitis, and polyarteritis nodosa in Norwich (east England population 413 500) and Lugo (northwest Spain population 204 100). Patients with PSV were identified between 1 January 1988 and 31 December 1998. RESULTS: Overall, the incidence of PSV in adults was almost equal in Norwich (18.9/million) and Spain (18.3/million). The incidence of Wegener's granulomatosis in Norwich (10.6/million) was greater than in Spain (4.9/million). There was a marked age-specific increase in incidence in Norwich with a peak age 65–74 years (52.9/million), but a virtually equal age distribution between ages 45 and 74 in Lugo (34.1/million). There was no significant increase with time in either population, or evidence of cyclical changes in incidence. CONCLUSION: These data support the suggestion that environmental factors may be important in the pathogenesis of PSV.